2015
DOI: 10.1002/adma.201500188
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Building Blocks and Their Boundary Interaction for the Creation of New, Potentially Superhard, Carbon Materials

Abstract: A strategy for preparing hybrid carbon structures with amorphous carbon clusters as hard building blocks by compressing a series of predesigned two-component fullerides is presented. In such constructed structures the building blocks and their boundaries can be tuned by changing the starting components, providing a way for the creation of new hard/superhard materials with desirable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
4
30
0
3
Order By: Relevance
“…The fact that these amorphous carbon clusters still form an orthorhombic structure suggests that the presence of the compressed and reacted C 8 H 8 can tune the boundary interactions of the carbon clusters to retain their ordered arrangement under high pressure. This is similar to the case of compressing solvated C 60 (C 60 ‐aromatic solvent), in which collapsed or highly deformed C 60 molecules act as hard building blocks while the long‐range periodic structure is preserved with their boundary tuned by the intercalated solvent molecules . We thus believe that a new ACC‐based ordered carbon phase is formed by compressing C 8 H 8 /C 60 cocrystal.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…The fact that these amorphous carbon clusters still form an orthorhombic structure suggests that the presence of the compressed and reacted C 8 H 8 can tune the boundary interactions of the carbon clusters to retain their ordered arrangement under high pressure. This is similar to the case of compressing solvated C 60 (C 60 ‐aromatic solvent), in which collapsed or highly deformed C 60 molecules act as hard building blocks while the long‐range periodic structure is preserved with their boundary tuned by the intercalated solvent molecules . We thus believe that a new ACC‐based ordered carbon phase is formed by compressing C 8 H 8 /C 60 cocrystal.…”
supporting
confidence: 64%
“…Remarkably, after 13 h at 45 GPa both the C 60 and C 8 H 8 molecules in the sample have completely collapsed and amorphized, as indicated by significant changes in the corresponding vibrational spectra of the released sample ( Figure a,b). The Raman spectrum of the released sample shows only two asymmetrical broad bands at 600–800 and 1100–1800 cm −1 (with the most intensive position at 1552 cm −1 ), assigned to vibrational modes of the CC/CC bonds in fullerenes or fullerene fragments, containing hexagonal and pentagonal carbon rings . A similar broad and asymmetric peak at 1552 cm −1 has also been observed in diamond‐like carbon film and in 3D C 60 polymers containing large amounts of sp 3 carbons .…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…The resulting material is incompressible and hard enough to indent diamond anvils (Yao et al, 2013). A recent study has shown that similar "super-hard" materials can be obtained from solvates of Buckminsterfullerene (but also of higher fullerenes such as C70) with several solvents (Yao et al, 2015). It is worth noticing that pristine C60 does not yield a super-hard material after compression at high pressure (Wang, 2015), hence, cocrystal formation is a prerequisite to obtain super-hard materials from fullerene precursors.…”
mentioning
confidence: 99%